Can Malaysia Meet Its Renewable Power Plant Expansion Target by 2015? Evidence from System Dynamics Model - Salman, Ahmad; Razman, Mat Tahar (Universiti Malaysia Pahang, 2013)
Malaysia having more than 65% of electricity generation from fossil fuels has been trying to incorporate renewable resources in the fuel mix. System Dynamics modelling and simulation approach is used to model capacity expansion target by 2015. The system dynamics model consists of construction, incentives and investors ' behavioral feedback, in making an investment decision. Analysis under optimistic settings reveals that investments fail to achieve the target of 985Megawatts of renewable capacity.